The Role of Social Entrepreneurs in Increasing Sustainability Values through Good Governance Practices: Case Study of Pesona Plastic in Bali - Wiryana, Kadek Velia Sita Devi; Mahyuni, Luh Putu (Ilomata International Journal of Management, 2025)
This research explores the role of social entrepreneurs in creating social impact through implementing good governance. Social entrepreneurs often combine business goals with social missions, using sustainable business models to address social issues such as poverty, the environment, and education. Good governance is the key to success because it ensures transparency, accountability, and inclusive participation in decision-making. This qualitative research highlights how good governance practices can strengthen the legitimacy and sustainability of social enterprises and increase positive impacts in society, especially in Bali. This research explores the role of social entrepreneurs in creating sustainable social impacts through the Theory of Change approach and the Penta Helix model. Theory of Change is used to formulate effective social transformation strategies by identifying the ultimate goal and the critical steps needed to achieve it. Meanwhile, the Penta Helix model facilitates collaboration between five key elements—government, academics, business, community, and media—to strengthen the social innovation ecosystem. This research highlights how social entrepreneurs can utilize these two approaches to strengthen good governance, increase accountability, and expand positive impacts on society through inclusive and sustainable partnerships.